Sea-Ice Production in Antarctic Coastal Polynyas Estimated From AMSR2 Data and Its Validation Using AMSR-E and SSM/I-SSMIS Data - Nihashi, Sohey; Ohshima, Kay I.; Tamura, Takeshi (IEEE journal of selected topics in applied earth observations and remote sensing, 2017)
Antarctic coastal polynyas are very high sea-ice production areas. The resultant large amount of brine rejection leads to the formation of dense water. The dense water forms Antarctic bottom water, which is the densest water in the global overturning circulation and a key player in climate change as a significant sink for heat and carbon dioxide. In this study, an algorithm was developed that uses Advanced Microwave Scanning Radiometer 2 (AMSR2) data (2012-present) to detect polynya area and estimates thin ice thickness by a method similar to that used to develop the algorithm for Advanced Microwave Scanning Radiometer for EOS (AMSR-E) data. Landfast sea-ice areas were also detected using AMSR2 data. Ice production in the polynyas was estimated by a heat flux calculation using AMSR2 sea-ice data. In four major polynyas, AMSR2 ice production was compared with AMSR-E (2003-2011) ice production through comparison of them with Special Sensor Microwave Imager (SSM/I) and Special Sensor Microwave Imager/Sounder (SSMIS) ice production. The comparison confirmed that the ice production from AMSR-E/2 data, which have higher spatial resolution than SSM/I-SSMIS data, can be used to analyze time series covering more than 10 years. For example, maps of annual ice production based on AMSR-E/2 data revealed detailed changes of the Mertz Polynya, where the ice production decreased significantly after the Mertz Glacier Tongue calving in 2010. Continuous monitoring of the coastal polynyas by the AMSR series sensors is essential for climate-change-related analyses in the Antarctic Ocean.